Teachers’ Strategies to Foster Students’ Creative Thinking Skills in Biology Learning: A Systematic Literature Review - Prasetyo, Opik; Ruwaida, Ulya; Aurora, Zevira Fansisca; Oktaviana, Rina; Fajeriadi, Heri; Aulia, Nurul; Rachman, Hening Triandika (Journal Of Biology Education Research (JBER), 2025)
Teachers play a pivotal role in designing innovative biology learning strategies that cultivate students' creative thinking, a core 21st century skill. This ability is essential for generating novel ideas, solving complex problems, and making interdisciplinary connections. By integrating real world scenarios and inquiry based approaches, teachers can further enhance students’ engagement and creative capacity. This study aims to conduct a systematic literature review to identify and analyze the pedagogical strategies employed by teachers to foster students' creative thinking skills in the context of biology learning. Employing the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) methods, a comprehensive literature search was executed using the Google scholar and Scopus database, with a publication scope from 2016 to 2025. The keywords used were ("Teacher Strategy") AND ("Creative thinking" OR "Creativity") AND ("Biology Learning" OR "Biology Education"). From an initial identification of 371 articles, 25 met the predefined inclusion criteria and were subsequently subjected to an in-depth content analysis. The review's findings indicate that a range of effective strategies were implemented by teachers, including Problem Based learning (PBL), Project Based Learning (PjBL), flipped classroom, blended-learning, the RQA model, Reading-concept mapping (Recamp) integrated with Group Investigation (GI), Creative Responsibility Based Learning (CRBL), and approaches grounded in ethnoscience and the Habits of Minds (HoM) profile. The most frequently utilized instructional media were mind maps, 3D learning media (3Ds Max), and inquiry based worksheets. This review recommends that pedagogical competence among biology teachers be enhanced through ongoing professional development and the integration of creative strategies into the curriculum. This will empower them to design innovative learning models that effectively foster students' creative thinking skills, addressing the demands of 21st century education.